PSIKOLOGI DAN KOMUNIKASI MASSA - Zulkarnain Zulkarnain (Universitas Islam Negeri (UIN) Mataram, 2015)
In this paper, the writer would like to investigatepsychology and mass communication which empty into values of social life both individual and group in communication. Human is truly social creature because, since borne, human needs intercourse with other people to fulfill biological needs, such as: eatingand drinking. Then process of human effort to know various kinds of stimulus or information comes to his/her senses, saves, connects, analyses, and solves the problems based on the stimulus or information, so psychology long time ago analyzed effect of mass communication in behavior of message receiver.